Influence Advertisement, Consumer Trust, Consumer Motivation Against Consumer Buying Interest at PT Darul Umroh Haramain Medan - Ade Prasetio; Rosinta Romauli Situmeang (Jurnal Mantik, 2021)
The purpose of this study is to test and analyze the effect of Advertisement, Consumer Trust, Consumer Motivationon Consumer Purchase Interest at PT Darul Umroh Haramain Medan. The population and sample in this study amounted to 64 consumers. The research method uses multiple linear regression analysis techniques.The results of the calculation of partial hypothesis testing obtained tcount > ttable or 2.806 > 2,000 and significant obtained 0.007 < 0.05,means that partially Advertisement positive and significant effect on Consumer Buying Interest at PT Darul Umroh Haramain Medan. The results of the calculation of partial hypothesis testing obtained tcount > ttable or 2,193 > 2,000 and significant obtained 0.032 < 0.05,means that partially consumer confidence has a positive and significant effect on consumer buying interest at PT Darul Umroh Haramain Medan. The results of the calculation of partial hypothesis testing obtained tcount > ttable or 2,059 > 2,000 and significant obtained 0,044 < 0,05,means that partially AdvertisementConsumer Motivationpositive and significant effect on Consumer Buying Interest at PT Darul Umroh Haramain Medan. The test results obtained the calculated F value (11.240) > F table (2.76) and a significance probability of 0.000 < 0.05, meaning that simultaneouslyAdvertisement, Consumer Trust, Consumer Motivationpositive and significant effect on Consumer Buying Interest at PT Darul Umroh Haramain Medan.